2003
DOI: 10.3354/dao057261
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus (WSSV) infectivity for Artemia at different developmental stages

Abstract: White spot syndrome virus (WSSV) is a major pathogen of cultivated shrimp, but its host range includes a large number of crustaceans. In this investigation, Artemia franciscana was tested for susceptibility to WSSV by the oral route. Both instars and adults were challenged, and the presence of WSSV was followed through to reproductive cysts and offspring using PCR. WSSV caused a much lower cumulative mortality in Artemia than in cultivated shrimp by 10 d post-challenge. Instars, adults and reproductive cysts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…In epizootiological surveys and experimental infection, WSSV-positive was detected on Artemia cysts and adults (Huang et al,1995b;Song et al, 2001;Sahul Hameed et al, 2002;Chang et al 2002;Li et al 2004;Deng et al, 2005). The present experiment gave similar results, which indicated that Artemia could be infected by WSSV and became carrier of the virus.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In epizootiological surveys and experimental infection, WSSV-positive was detected on Artemia cysts and adults (Huang et al,1995b;Song et al, 2001;Sahul Hameed et al, 2002;Chang et al 2002;Li et al 2004;Deng et al, 2005). The present experiment gave similar results, which indicated that Artemia could be infected by WSSV and became carrier of the virus.…”
Section: Resultsmentioning
confidence: 95%
“…In the oral route of infection, Artemia were fed with the mixture of rice bran and WSSV. However, Li et al (2004) fed Artemia with viral feeding mixture (VFM) in which WSSV were mixed with powdered algae. Then, Li et al (2004) found that Artemia and their reproductive cysts become WSSV positive by one step PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrobrachium rosenbergii nodavirus (MrNV; the causative agent of white tail disease) and extra small virus (XSV) can be vertically transmitted (Sudha ka -ran et al 2007). Rotifers naturally exposed to sediments with WSSV passed the virus to their eggs (Yan et al 2004), and the virus appears to use vertical transmission in brine shrimp as well (Li et al 2003). Infectious hypodermal and hemato poietic necrosis virus (IHHNV) of shrimp uses vertical transmission in hosts that survive the acute stages of infection (Motte et al 2003).…”
Section: Discussionmentioning
confidence: 99%